Hubungan Strategi Marketing Public Relations dalam Membangun Brand Image PT. GK Invest - Rianti Haifa Khoirunissa; Riza Hernawati (Bandung Conference Series: Public Relations, 2023)
Abstract. Marketing Public Relations is one of the important things in a company, especially in the Business World. The concept of a marketing public relations strategy can help the development of companies that can improve the brand image of a company, maintaining relationships with the community can further help companies to move better. With a case related to fraudulent investment in the luring of getting short-term profits and being given directions to make accurate investments in the timing of attracting transactions, I took research on "Marketing Public Relations Strategies in Building a Brand Image of PT. Gk Invest". This study aims to find out how the marketing public relations strategy through the Pull Strategy, Push Strategy and Pass Strategy carried out by PT. GK Invest Bandung in building a Brand Image. The method used in this research is quantitative method with descriptive analysis. The number of samples is 100 respondents. Data collection techniques in this study were divided into primary data and secondary data. The data analysis technique used is validity test and reliability test. The results of this study indicate that there is an increase in brand image that occurs in GK.Invest after implementing a marketing public relations strategy both in a pull strategy, push strategy and pass strategy. Keywords: Strategy, Marketing, Public Relations, Brand Image Abstrak. Marketing Public Relations merupakan salah satu hal yang penting dalam sebuah perusahaan terutama dalam Dunia Bisnis. Konsep strategi marketing public relations dapat membantu pengembangan perusahaan yang dapat meningkatkan brand image pada suatu perusahaan, menjaga hubungan dengan masyarakat dapat lebih membantu perusahaan untuk melangkah lebih baik. Dengan adanya kasus terkait penipuan ber-investasi yang di iming-imingin mendapatkan keuntungan jangka pendek dan diberikan arahan untuk melakukan investasi yang akurat dalam timing menarik transaksi, maka saya mengambil penelitian tentang “Strategi Marketing Public Relations Dalam Membangun Brand Image PT. Gk Invest”. Penelitian ini bertujuan untuk mengetahui bagaimana strategi marketing public relations melalui Pull Strategy, Push Strategy dan Pass Strategy yang dilakukan oleh PT. GK Invest Bandung dalam membangun Brand Image. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan analisis korelasi. Jumlah sampel sebanyak 100 responden. Teknik pengumpulan data pada penelitian ini terbagi atas data primer dan data sekunder. Teknik analisis data yang dilakukan adalah uji validitas dan uji reliabilitas. Hasil pada penelitian ini menunjukan bahwa adanya peningkatan brand image yang terjadi pada GK.Invest setelah menerapkan strategi marketing public relations baik secara pull strategy, push strategy dan pass strategy. Kata Kunci: Strategi, Marketing, Public Relations, Brand Image